Some Remarks on the ‘Shechita Case’ of the ECJ - Marinkás, György (Law, Identity and Values, 2021)
This study strives to answer why the European Court of Justice’s (ECJ) ‘Centraal Israëlitisch Consistorie van België’ judgment, delivered on 17 December 2020, triggered heated reactions. Similarly, sharp criticisms were articulated regarding the recent decision of the Belgian Constitutional Court (Grondwettelijk Hof), where the Court upheld the national legislation on the ban of slaughter without prior stunning per the aforementioned ECJ judgment. This study examines the historic, theological, and scientific background of shechita and halal slaughter with reference to the aforementioned framework. Furthermore, the study strives to introduce the pros and cons of the issue to help the reader decide whether the ritual slaughter — the slaughter of animals without prior stunning but following certain rules aimed at sparing animals from useless suffering — is as humane as the modern non-religious method, where the slaughter is conducted with prior stunning. This study also examines the different theological interpretations on the acceptability of stunning animals before slaughter. In the second part, the study briefly introduces the freedom of religion-related case law of the European Court of Human Rights, and thoroughly analyses its Cha’are Shalom ve Tsedek decision. Moreover, it examines the ECJ’s two ritual slaughter cases, namely the Liga van Moskeeën and Œuvre d’assistance cases, which preceded the Centraal Israëlitisch Consistorie van België case. As a brief excursus into the jurisprudence of the national constitutional courts, this study also introduces two cases brought by the constitutional courts of Germany and Poland. Finally, the third part thoroughly analyses the Advocate General’s opinion and the judgment delivered in the Centraal Israëlitisch Consistorie van België case of the ECJ to highlight the reasons for the different interpretations of the very same EU law.